KAJIAN LITERATUR TENTANG PENDEKATAN KONTEKSTUAL DALAM MENINGKATKAN KETERAMPILAN MENULIS SISWA SEKOLAH DASAR - Afaf Atiqah; Sebayang, Apri Boy; Ningsi, Bahagia Fitri; Chalaska, Nadia; Daulay, Siti Yuli Khairani; Juliati, Juliati (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to systematically examine the application of the contextual approach (Contextual Teaching and Learning/CTL) in improving the writing skills of elementary school students. The method used is a systematic literature review by analyzing various articles and scientific books relevant to writing learning and the contextual approach. The results of the study show that the CTL approach is able to create meaningful learning by linking the material to the students' real experiences. This approach has been proven to increase students' active engagement, creativity, and ability to express ideas and thoughts in writing. In addition, CTL helps students understand the material more deeply and retain it longer in their memory. Therefore, the contextual approach is recommended as an alternative effective learning strategy to improve the writing skills of elementary school students.